Magnetic BiFeO3 grafted with MWCNT hybrids as advanced photocatalysts for removing organic contamination with a high concentration. Issue 55 (20th May 2016) - Wang, XiaoFei; Fan, JinChen; Qian, Fei; Min, YuLin
Abstract : This work focuses on a novel visible light responsive photocatalysis system for removing organic contamination employing MWCNTs as a scaffold and an efficient electron relay mediator and visible light and magnetically responsive BiFeO3 . Abstract : This work focuses on a novel visible light responsive photocatalysis system for removing organic contamination in a high concentration, employing MWCNTs as a scaffold and an efficient electron relay mediator and visible light and magnetically responsive BiFeO3 . The MWCNT grafted BiFeO3 composites are fabricated by annealing an acid-functional MWCNT and Bi–Fe complex mixture at 800 °C, which induces the in situ formation of BiFeO3 particles that are grafted with the MWCNT matrix. The optimal BiFeO3 /MWCNT photocatalyst exhibits enhanced photocatalytic activity under visible light, ascribed to efficient charge separation and transport which greatly extends the electron life time using MWCNTs as an electron acceptor. Simultaneously, the high surface area of the BiFeO3 /MWCNT photocatalyst can act as an adsorbent to reduce organic contamination of a high concentration under an external magnetic field. The two processes composed of physical adsorption and photocatalytic degradation result in the fast removal of organic contamination during a short reaction time compared to N-doped TiO2 . This work not only provides a new strategy for the fabrication of high performance multimetallic oxide grafted MWCNT photocatalysts, but also facilitates their practical application in environmental issues.